Upaya Satuan Polisi Pamong Praja (SATPOL PP) Dalam Menertibkan Prostitusi Terselubung Pada Tempat Karaoke Di Kota Padang - Ismail Agus Saputra; susi delmiati; Rianda prima putri (CV. ITTC INDONESIA, 2023)
Prostitution has been an enduring phenomenon in Indonesia for an extended period of time. Prostitution is the sale of human beings for financial gain, among other motives. The jurisdiction over prostitution in Padang is transferred to the Padang City Satpol PP, as stipulated in Chapter 1, Article 1 of the Regional Regulation of the City of Padang Number 11 of 2005 pertaining to General Provisions. Several issues can be deduced from the preceding description, including the following: What is the function of the Satpol PP in overseeing clandestine prostitution at karaoke establishments in Padang City? Furthermore, what challenges does Satpol PP face when attempting to regulate clandestine prostitution in Padang City's karaoke establishments? The study employs a sociological juridical methodology. Both primary and secondary data are utilised. Methods of data collection include document analysis and interviews. The data underwent qualitative analysis. The findings of the study indicate that effective control by Satpol PP is contingent upon the proper operation of nightly patrols, regulations, and stringent measures implemented by Satpol PP. Two factors impeded the Padang City Satpol PP's ability to control karaoke: internal constraints, such as raid information leaks, and external obstacles, such as the large number of TNI personnel who own karaoke and the protection it receives from other officials, which prevented the Satpol PP from conducting policing.